Integration of Maqāṣid al-Syarī'ah and Social Justice: Reconfiguring the Legal Status of Children Born Out of Wedlock in Islamic Law and the Indonesian Legal System - Muhammad Hafis; Juliani Syafitri; Rafi'aturrahmah Rafi'aturrahmah; Johari Johari (Baitul Hikmah: Jurnal Ilmiah Keislaman, 2025)
This article explores the redefinition of the status of children born out of wedlock by integrating maqasid al-syariah and social justice. This study departs from the dominant classical Islamic legal construct, which severs the relationship between a child and his biological father. This restrictive approach, although intended to prevent adultery (sadd al-dhari'ah), actually causes injustice by neglecting the protection of innocent children. The research uses a normative-theological and sociological approach to analyze the dialectic between classical Islamic law and Indonesian positive law. Supreme Court Decision No. 46/PUU-VII/2010 is an important milestone that recognizes the relationship between children and their biological fathers based on scientific evidence. The ethical justification lies in the framework of maqāṣid al-sharī'ah, particularly the protection of life (ḥifẓ al-nafs), honor (ḥifẓ al-'ird), and lineage (ḥifẓ al-nasl) in a more substantive manner. Criticism and deconstruction from the perspective of justice and maqāṣid offer a new legal-ethical framework centered on the interests of the child. Ḥifẓ al-nasl is not only about preserving lineage, but also guaranteeing the basic rights of children. Meanwhile, ḥifẓ al-'ird becomes a synthesis to protect the honor of children from discrimination. The integration of maqasid al-syariah and social justice paves the way for a more inclusive, humanistic, and relevant study of Indonesian Islamic family law in the face of contemporary challenges.